Frequency of Hypomagnesemia in Patients with Chronic Obstructive Pulmonary Disease (COPD) - Muhammamd Jamil, Muhammad Uzair Siddique, Munawar Hussain Shah, Rana Khalid Mahmood, Nabeel Ahmad, Masood Alam, Muhammad Ibrahim (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to assess the prevalence of hypomagnesemia among COPD patients (COPD). Study design: A cross sectional study. Place and duration of study: I have been offered a position in the Medicine & Pulmonology Department at Nishtar Hospital in Multan, Pakistan, which I will begin in March 2016 and remain in until February 2018. Methodology: The non-probabilistic sequential sampling technique used to choose the final pool of 137 cases. Quantitative variables’ means and standard deviations were determined. Quantitative evaluation included frequency counts and percentages for qualitative factors. Several effect modifiers have been taken into consideration via stratification, including age, diabetes, body mass index, COPD, high blood pressure, smoking, socioeconomic status, place of residence (race/ethnicity), and gender. A chi-square test for stratification was used to examine the data, and a P value of 0.05 was considered statistically significant. Results: 30.81±14.74 Nearly eighty-one percent of the sample had illnesses that lasted more than 18 months, and the median duration of illness was also months (112). Fifty patients, or 36.5% of the total, were found to have low magnesium levels, with a mean blood magnesium level of 1.520.54 meq/liter. Practical Implementation: There is a lack of data on the function of magnesium in preventing COPD exacerbations. Hypomagnesemia may prove to be helpful in establishing COPD exacerbation as a predictive factor, according to the research that is now being conducted. This could lead to the development of COPD intervention strategies other than the standard treatments, enhancing COPD patients’ life quality, morbidity, and mortality. Conclusion: Our results provide evidence that hypomagnesemia is common among people with COPD. Male gender, greater age, lower socioeconomic status, diabetes, hypertension, tobacco use, and longer disease duration were all associated with low magnesium levels. Keywords: Chronic Obstructive pulmonary disease (COPD), frequency, hypomagnesemia.